Evaluasi Fisik Sediaan Tablet Amlodipine (Besilat) sebagai Obat Antihipertensi: Perbandingan antara Tablet Generik dan Generik Bermerek - Laelatul Husniyah; Anggita Dipika Wulandari; Hafidz Muzaki (Lembaga Pengembangan Kinerja Dosen, 2025)
Popular antihypertensive drugs used are amlodipine (besylate) in generic and branded generic tablets. To ensure that a drug is of good quality and efficacy, evaluation of the physical quality of the tablet is very important. This study aims to determine the results of the physical evaluation of generic and branded amlodipine (besylate) tablets that are currently available for purchase. This type of experimental study involves random sample selection. Testing was carried out on three samples of generic amlodipine (besylate) tablets and one sample of branded generic tablets. The physical evaluation of the tablets carried out was uniformity of weight, uniformity of size, hardness, friability, and disintegration time as part of the physical examination. The test results showed that generic tablets 3 and branded generics met the requirements of the Indonesian Pharmacopoeia.